Effectiveness of the AngoLingo Mobile Game Technology in English Language Learning in Adamson University Basic Education Department - Andalis, Allhyn Marie; Henson, Benedict Clarence; Junsay, Julie Anne; Makan, King David; Renen-Dela Cruz, Gloria (JPAIR Multidisciplinary Research, 2017)
Technology is gradually shifting the focus of learning to less traditional methods; like eBooks, audiobooks, and more recently, mobile applications. This shift indicates an apparent need to incorporate entertaining components into learning tools to keep users engaged in critical thinking, and comprehension activities. There is untapped power in mobile entertainment, particularly mobile games that can and must be harnessed to improve current methods, and even introduce new methods of learning English. This study seeks to determine the effectiveness of AngloLingo, a mobile game that is built on the basics of English, in facilitating learning of English vocabulary, spelling and grammar in students in the Basic Education Department of Adamson University, Philippines. A control group (N=18) and an experimental group (N=18), were used during the test. Quasi-Experimental Research Design with pretest and posttest was used to determine the difference in performance between the control and experimental groups. Results indicate a significant improvement in performance on the post-test of the experimental group due to the use of AngloLingo before administration of the posttest. The overall results of the three sub-tests (P-Value = 6.39E-08) indicate the effectiveness of AngloLingo in learning Basic English vocabulary, spelling, and grammar. This study also offers recommendations on the incorporation of mobile games in teaching and learning Basic English.
Keywords: English language learning; mobile game; Basic English; vocabulary; spelling; grammar